Mutual mate preferences and assortative mating in relation to a carotenoid-based color trait in blue tits - Caro, Samuel P; Pierre, Léo; Bergès, Matthieu; Bakker, Raldi; Doutrelant, Claire; Bonadonna, Francesco (Behavioral ecology, 2021)
Abstract Choosing an appropriate sexual partner is a critical decision for many animal species. However, many mechanisms involved in mate choice are still poorly understood. Do both males and females choose their sexual partners, do both sexes use the same criteria for choosing, and do their own phenotype influence the choices they make, are questions that need further investigation. Over two successive experiments conducted in captivity with hand-reared blue tits (Cyanistes caeruleus), we manipulated the color of the chest plumage, a secondary sexual trait that reflects an individual’s condition, to create two different color morphs (one pale and one colored). We then tested whether both sexes express a preference, whether they are attracted to the same morphs, and if the subjects’ own chest color influences the preference they show. Our data reveal that both sexes are choosy, with females tending to be slightly choosier than males. We also show that both sexes preferentially select individuals with a pale chest plumage over colorful individuals, and this was again more pronounced in females. Finally, paler individuals tend to be selected by birds that are themselves pale, even if this phenotype matching was not very robust. Such a preference for paler individuals is intriguing because mates are predicted to associate with individuals displaying higher, not lower, value of quality signals. It could result from adaptive mechanisms related to avoidance of aggressiveness in a confined environment, avoidance of conflicting sexual signals within individuals, or from cultural mechanisms leading to a preference for individuals that match its own phenotype. Blue tits do not always prefer sexy partners. We asked male and female blue tits to express a preference between potential mates whose plumage was either colorful or dull, and found that they preferred duller birds. Furthermore, and contrary to what is often described in the literature, we also found that males do not only show off, but also express partner preferences.